Entre os espaços e a cidade : a insurgência do skate na experiência urbana contemporânea - Böes, Guilherme Michelotto (2017)
The city and contemporary urban space are undergoing significant influences from new cultural relations. Urban sociology has advanced in the studies on urban public spaces between the environment of practices, behaviors, cultures and policies. Thus, urban space presents itself as a relation of power of socio-cultural dynamics between the values and meanings of public life. Understanding these cultural phenomena that emerge in the spaces of the cities are fundamental to advance in ethnographic data that exploring the cultures between and through the places where the activities and the values prospect insurgencies in the urban spaces. In order to explain the formation of the cultural space in the city, it is necessary to analyze the urban space of the city, with its uses and counter-uses, to present the significant processes of influence of globalization in the planning of urban public spaces. The urban experience by means of the skateboarding in the spaces of the cities demands to find its rhythm on the conception between the public and the private, its urban structure put in tension to its space of use. In this approach, skateboarding reveals contemporary urban experience as a continuous process of contesting watertight social values, the democratization of urban public space, the destruction of value systems and the continuous formation of plural itineraries, whether as leisure, communication or social interaction . This urban experience reveals new ways for the social sciences to reflect critically on city spaces and their continuous practices, identifying the formative processes present in contemporary urban cultures and locating the genesis of spaces in cities.